Hard markets, hard times: On the inefficiency of the CAT bond market - Götze, Tobias; Gürtler, Marc (Journal of Corporate Finance, 2020)
This study explores the existence of inefficiencies in catastrophe (CAT) bond secondary markets by investigating the impact of sponsor characteristics on the CAT bond premium. We show that the CAT bond market does not satisfy the demand for catastrophe risk transfer efficiently by revealing a significant effect of sponsor-related factors on the CAT bond premium. This inefficiency is particularly surprising given that a CAT bond isolates the insured risk from other sponsor-related risks through a special purpose vehicle. Remarkably, this inefficiency is even present among non-indemnity CAT bonds, which determine the payout through a mechanism that is exogenous to the sponsor. Our findings also reveal that sponsor-related pricing inefficiencies vary over time and are more relevant during hard and neutral phases compared to soft market phases. Among the sponsor-related determinants of the CAT bond premium are the sponsor's tenure, market coverage, rating, credit default swap spread, and his ability to issue innovative “on the run” CAT bonds.